2019
DOI: 10.5194/amt-12-4113-2019
|View full text |Cite
|
Sign up to set email alerts
|

Tropopause altitude determination from temperature profile measurements of reduced vertical resolution

Abstract: Abstract. Inference of the lapse rate tropopause or the cold point from temperature profiles of finite vertical resolution entails an uncertainty of the tropopause altitude. For tropical radiosonde profiles the tropopause altitude inferred from coarse-grid profiles was found to be lower than that inferred from the original profiles. The mean (median) displacements of the lapse rate tropopause altitude when inferred from a temperature profile of 3 km vertical resolution and a Gaussian kernel are −130, −400, −73… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…However, the magnitude of the warm bias is roughly 2-3 times smaller compared to Bland et al (2021). This difference may be related to vertical smoothing of the radiosonde profiles in Bland et al (2021), which could lead to a higher tropopause temperature (König et al, 2019). Large N² biases (-2 to 3x10 -4 s -2 ) in the analysis are found in the ±0.5 km layer around the tropopause.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…However, the magnitude of the warm bias is roughly 2-3 times smaller compared to Bland et al (2021). This difference may be related to vertical smoothing of the radiosonde profiles in Bland et al (2021), which could lead to a higher tropopause temperature (König et al, 2019). Large N² biases (-2 to 3x10 -4 s -2 ) in the analysis are found in the ±0.5 km layer around the tropopause.…”
Section: Discussionmentioning
confidence: 77%
“…Bland et al (2021) showed a higher tropopause altitude of about 200 m in IFS analyses using a previous model cycle (Cy41r2) and 3204 radiosondes that are a subset of the data set analysed in this study. Again, the differing results may be related to the vertical smoothing of the radiosonde profiles (König et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Of course, the new method can also assist the researches on tropopause inversion layer characteristics. o N], which may be related to the different vertical resolution of temperature profiles provided by various data sources (König et al, 2019;Hoffmann and Spang, 2022;Pan et al, 2004;Wang et al, 2019). Moreover, tropopause structures over the Tibetan Plateau differ from those in the same latitudinal zone, likely due to unique atmospheric circulation structures such as the Asian summer monsoon anticyclone, planetary wave breaking and uploading, orographic gravity waves, and atmospheric temperature disturbances in the UTLS.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of only focusing on the average temperature lapse rates, we define the temperature‐based tropopause as the pressure above the boundary layer at which: dT/dh crosses from being negative to being positive. This effectively corresponds to the so‐called “cold‐point tropopause” which is often used instead of the WMO definition for tropical regions (Highwood & Hoskins, 1998; Kim & Son, 2012; Laura L. Pan et al., 2018; Mehta et al., 2008; Zhou et al., 2001), but can also be used for extratropical regions (König et al., 2019). dT/dh and dT/dP begin to oscillate wildly. …”
Section: Methodsmentioning
confidence: 99%
“…dT/dh crosses from being negative to being positive. This effectively corresponds to the so‐called “cold‐point tropopause” which is often used instead of the WMO definition for tropical regions (Highwood & Hoskins, 1998; Kim & Son, 2012; Laura L. Pan et al., 2018; Mehta et al., 2008; Zhou et al., 2001), but can also be used for extratropical regions (König et al., 2019).…”
Section: Methodsmentioning
confidence: 99%